Drag Analysis from PIV Data in Speed Sports. (2016) - Terra, W.; Sciacchitano, A.; Scarano, F.
Abstract: Aerodynamic drag is computed from velocity measurements obtained with particle image velocimetry (PIV). This allows determining the drag force in combination with the visualization of the flow structures responsible for drag generation. Two experiments are conducted to illustrate the working principle of the approach, which is meant for applications in speed sports. The first experiment assesses the aerodynamic effect of surface roughness by measuring the flow over a circular cylinder dressed in a rough fabric used in professional cycling. The application of roughness can reduce the drag by about 30% with respect to a smooth surface. The second experiment demonstrates at small scale a possible approach to directly study the aerodynamic drag associated to moving athletes. This offers an alternative to the measurements in wind tunnels, where only stationary cases are practically studied. A system towing a sphere of 16 cm diameter is used to demonstrate the concept. Drag coefficient calculations come to agree with literature data within 15%.